New Zealand: Country Report on Human Rights - Baird, Natalie; Glazebrook, Susan; Holden, Sasha (Victoria University of Wellington Law Review, 2009)
This article provides a country report on the status of human rights in New Zealand. The article covers New Zealand's adherence to the rule of law, culture and language, education system, health system and environmental rights. The authors draw conclusions from each section: New Zealand's commitment to the rule of law is generally strong, albeit with concerns regarding access to justice. Positive developments were undertaken regarding language but disappointing in its indigenous rights. The right to education is generally secure, but some vulnerabilities remain. New Zealand has a generally favourable health services system. Finally, although New Zealand's legal framework does not recognise the right to an environment of a particular quality, the Resource Management Act 1991 provides a strong participatory framework.